Aggrecanases and cartilage matrix degradation. - Nagase, H; Kashiwagi, M (2003)
The loss of extracellular matrix macromolecules from the cartilage results in serious impairment of joint function. Metalloproteinases called 'aggrecanases' that cleave the Glu373-Ala374 bond of the aggrecan core protein play a key role in the early stages of cartilage destruction in rheumatoid arthritis and in osteoarthritis. Three members of the ADAMTS family of proteinases, ADAMTS-1, ADAMTS-4 and ADAMTS-5, have been identified as aggrecanases. Matrix metalloproteinases, which are also found in arthritic joints, cleave aggrecans, but at a distinct site from the aggrecanases (i.e. Asn341-Phe342). The present review discuss the enzymatic properties of the three known aggrecanases, the regulation of their activities, and their role in cartilage matrix breakdown during the development of arthritis in relation to the action of matrix metalloproteinases.